Cardiac effects of echinocandins after central venous administration in adult rats - Koch, Christian; Uhle, Florian; Wolff, Matthias; Arens, Christoph; Schulte, Astrid; Li, Ling; Niemann, Bernd; Henrich, Michael; Rohrbach, Susanne; Weigand, Markus A.; Lichtenstern, Christoph (Antimicrobial agents and chemotherapy, 2014)
Echinocandins have become the agents of choice for early and specific antifungal treatment in critically ill patients. In vitro studies and clinical case reports revealed a possible impact of echinocandin treatment on cardiac function. The aim of our study was to evaluate echinocandin-induced cardiac failure. Using an in vivo rat model, we assessed hemodynamic parameters and time to hemodynamic failure after central venous application (vena jugularis interna) of anidulafungin (low-dose group, 2.5 mg/kg body weight [BW]; high-dose group, 25 mg/kg BW), caspofungin (low-dose group, 0.875 mg/kg BW; high-dose group, 8.75 mg/kg BW), micafungin (low-dose group, 3 mg/kg BW; high-dose group, 30 mg/kg BW), and placebo (0.9% sodium chloride). Left ventricular heart tissue was collected to determine mitochondrial enzyme activity via spectrophotometric measurements. mRNA expression of transcriptional regulators and primary mitochondrial transcripts, mitochondrial DNA (mtDNA) content, and citrate synthase activity were also explored. Animals receiving high-dose anidulafungin or caspofungin showed an immediate decrease in hemodynamic function. All of the subjects in these groups died during the observation period. Every animal in the untreated control group survived (P < 0.001). Hemodynamic failure was not noticed in the anidulafungin and caspofungin low-dose groups. Micafungin had no impact on cardiac function. In analyzing mitochondrial enzyme activity and mitochondrial transcripts, we found no association between echinocandin administration and the risk for hemodynamic failure. Further experimental studies are needed to elucidate the underlying mechanisms involved in cardiotoxic echinocandin effects. In addition, randomized controlled clinical trials are needed to explore the clinical impact of echinocandin treatment in critically ill patients.
Gesehen am 27.09.2017